Pendampingan Komunitas Atlet Bola Voli Melalui Pelatihan Virtual Goal Setting untuk Meningkatkan Motivasi Berprestasi pada Masa Pandemi Covid-19 - Anatasya Divina; Aninditya Radini; Fransiska Julia; Khalisa Azilia; Muhammad Abiyyu; Marselius Sampe Tondok (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
During the Covid-19 pandemic, the Petrokimia Gresik Volleyball Club’s female athletes have to do training from home (TFH). Unfortunately, this prolonged TFH has caused the athletes to experience a decrease in motivation and training goals. This community service aimed to increase the athletes’ achievement motivation through a Virtual Goal Setting Training (VGST). The methods used to facilitate the partners’ skill formation in designing SMART goal-setting were lecturing, coaching, individual, and group discussion. The achievement motivation was measured by Achievement Motivation Scale for Specialists of the Sport for All (AMSSSA) as well as by observation and interviews. The results revealed that VGST could increase not only the athlete’s skill in designing SMART goal setting but also their motivation to engage in the Training from Home (TFH) Program individually and in a group. Therefore, a well-structured VGST’s design can be an alternative to increase the athlete’s achievement motivation during the Covid-19 pandemic